PERSEPSI PEMUSTAKA TERHADAP LAYANAN PERPUSTAKAAN IAIN BATUSANGKAR - Dela Karliza; M Haviz; Cut Afrina (JURNAL ILMU PERPUSTAKAAN (JIPER), 2022)
This research entitled “User Perception Towards Services At Library Of IAIN Batusangkar”. The purpose of this research is to find out how the user’s perception of IAIN Batusangkar Library Servives. The method used in this research is descriptive quantitative method. Researcher collected data by distributing questionaires to 55 respondents who became the research sample. The result of  research on user’s perception of IAIN Batusangkar library services obtained that the user perception variable had an average score of 3.22, the library variable had an average score of 3.17 and total average score of 3.19 with score range between 0-4. So it can be said that the user’s perception of IAIN Batusangkar library services is good. Hypothesis test results show that the significance value is 0.000 < 0.05 with a correlation coefficient value of 0.804, so it can be said there is a positive relationship between user perception and library services.